COMPLIANCE AS A PREVENTION TOOL AGAINST BUSINESS CRIME A VIEW FROM MODERN CRIMINOLOGY - Espinoza Bonifaz, Renzo (2017)
This research work seeks to analyze from a criminological view the compliance as a crime prevention  tool  within  the  legal  entities.  In order to do so, it is necessary to use modern criminological theories of greater scientific importance, in order to understand the raison d’être of compliance within a company, and ensure its best use as a state criminological policy. Likewise, a historical account of its genesis at the international level and of its incorporation in the  Peruvian  legal  system is made.